Visual representations in crime prevention: exploring the use of building information modelling (BIM) to investigate burglary and crime prevention through environmental design (CPTED) - Cozens, P. M. (Crime prevention and community safety, 2018)
Criminological research has long utilized visual representations of environments in seeking to explore perceptions of crime and personal safety and to investigate the relevance of specific design and security features. Much of this research has been in the field of environmental psychology and crime prevention through environmental design (CPTED). This paper traces the development of visual representations and the use of environmental stimuli in criminological research. We briefly review the contributions made by various visual media, including maps and drawings, photographs, models, video, virtual reality and gaming engines. These developments in visualization, building design and management technology have drastically improved the realism of representations of environments, and the potential for more standardized, widespread exploration and application of CPTED principles to reduce crime. To scope and evaluate the future potential of such emergent technologies, we critically review the literature concerned with virtual reality and building information technology (BIM), outlining uses in practice and new opportunities for criminological research. We frame the discussion with specific focus on analysing proposed residential dwellings to reduce vulnerability to burglary. A layered exploration for how BIM technologies may assist in implementing increasingly sophisticated assessments of crime vulnerability for proposed residential building designs brings the paper to a close. These discussions provide both a comprehensive overview for interested practitioners and chart specific opportunities for further research.